IMPLEMENTASI METODE RAPID APLICATION DEVELOPMENT (RAD) DALAM RANCANGAN SISTEM INFORMASI PELAYANAN ADMINISTRASI DI KELURAHAN TABAM KOTA TERNATE - Junaidi Sabtu; Rachmat Saleh Sukur; M Kasyif Gufran Umar (Jurnal Teknoinfo, 2022)
Tabam Village is one of the villages in North Ternate City with a modern community background, where smartphones and laptops are no longer new items for the local community. However, the administrative management system in the sub-district is still far from expectations in the current era. The administrative management system starting from making Identity Cards, Family Cards, Birth Certificates to Death Certificates is still conventional. This kind of administrative management system is believed to have many weaknesses such as paper wastage, interference with computer media and requires a long time to process one letter. How is the implementation of the Rapid Application Development (RAD) method in the design of the administrative information system in Tabam village. The research objective is to determine the implementation of the Rapid Application Development (RAD) method in the design of administrative information systems in Tabam village. The research method carried out in the study there are several methods, namely, conducting observations to see directly the administrative services in the output office, as well as conducting library studies to review relevant previous research journals and conducting studies on books related to research. The research system or application design uses the Rapid Application Development (RAD) method in several phases or stages, namely the Requirement Planning stage, the Design stage, and the Implementation stage.